Intangible Culture on Inland Seas, from Hudson Bay to Canadian Heritage - Brown, Jennifer (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
The author of this article examines the ways in which the Convention for the Safeguarding of Intangible Cultural Heritage considers the protection of aboriginal languages and provides a case study of the challenges of the preservation of the Cree language in Canada. For Indigenous people, in Canada as elsewhere, questions arise about who speaks for whom; many of their constituents may not identify with the major political organizations that represent their interests to governments and are recognized by government agencies; and other structural and logistical barriers also arise. The paper takes a look at the richness of Aboriginal history around Hudson Bay as held in language and stories, and then discusses the many challenges that a Hudson Bay Cree storyteller, Louis Bird, and his collaborators faced in pursuing an oral history project funded by a Canadian governmental agency with its own parameters and priorities.